Synthesis and characterization of zinc oxide nanoparticles using peppermint tea (mentha piperita) dregs extract and their photocatalytic performance - Loh, Xue Lin (2022)
Nanoparticles are classified as materials with a scale ranging from 1-100 nm. Nanoparticles are of profound scientific interest because they span the gap between bulk materials and atomic or molecular structures. Zinc oxide is a n-type semiconductor with a wide band gap of 3.37 eV and a large excitation binding energy of 60 meV. It is widely used in electronics, optoelectronics and laser technology. Zinc oxide nanoparticles is considered as one of the best photocatalyst for the degradation of pollutants in water since it has large surface area that enhances the photocatalytic activity. The aim of this project is to study the possibility of using peppermint tea dregs extract as the agricultural waste with zinc nitrate hexahydrate as salt precursor to synthesise zinc oxide nanoparticles through a simple, low cost, greener and environmentally friendly pathway. The qualitative phytochemical screening of peppermint tea dregs extract revealed the presence of flavonoids which can be served as the reducing agent and stabilising agent in the synthesis of zinc oxide nanoparticles. In addition, the effects of mass of zinc nitrate hexahydrate used and calcination temperature on the synthesis of zinc oxide nanoparticles were also studied. The synthesised zinc oxide nanoparticles were characterised via various analytical techniques such as Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray analysis (EDX) and particle size analysis (PSA). The photocatalytic performance of zinc oxide nanoparticles synthesised was evaluated by the degradation of crystal violet dye in aqueous solution with exposure to sunlight. The extent of dye degradation was monitored by using UV-Vis spectrophotometer.